NATURE STUDY OF DEFORMATION "ROUND PILE - RAFT" UNDER THE INFLUENCE OF VERTICAL AND HORIZONTAL LOADS - , В. Я.; , А. Н. (Municipal economy of cities (Technical science), 2013)
The analysis of the full-scale tests on a single foundation of bored pile on the effect of vertical and horizontal loads, offers advice on the foundation on single bored piles.